2007
DOI: 10.1002/ceat.200700193
|View full text |Cite
|
Sign up to set email alerts
|

Properties of BaAl2O4 in the Simultaneous Removal of Soot and NOx

Abstract: The catalytic activity of BaAl 2 O 4 in the simultaneous removal of soot and NO x was evaluated by Temperature Programmed Reaction (TPR). It was found that BaAl 2 O 4 could effectively catalyze the reaction of soot with NO x under various reaction conditions. Compared with non-catalytic combustion, ignition temperature, T ig , and maximum combustion temperature, T m , of soot decreased by more than 175°C and 240°C, respectively. Tight contact of soot with BaAl 2 O 4 , higher O 2 content and a lower flow rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 37 publications
1
18
1
Order By: Relevance
“…It was found that the activity of the catalyst was closely related to the O 2 concentration in the NO-containing stream [6][7][8]. In previous work by the current authors [1], it has been demonstrated that the activity of BaAl 2 O 4 is negligible and that N 2 O is not produced in the absence of oxygen. However, the activity and the N 2 O production level increase markedly under excess oxygen conditions.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…It was found that the activity of the catalyst was closely related to the O 2 concentration in the NO-containing stream [6][7][8]. In previous work by the current authors [1], it has been demonstrated that the activity of BaAl 2 O 4 is negligible and that N 2 O is not produced in the absence of oxygen. However, the activity and the N 2 O production level increase markedly under excess oxygen conditions.…”
Section: Introductionmentioning
confidence: 91%
“…2a), and the weak bands at 1385 and 1744 cm -1 are observed at the same time. These results suggest that the formation of nitrates is due to the oxidation of nitrites by lattice oxygen [1,15]. After feed- Figure 1.…”
Section: Effects Of O 2 Concentration On the No X Adsorbed On Baal 2 Omentioning
confidence: 99%
See 3 more Smart Citations